Distribution and spatial autocorrelation of the hospitalizations for cardiovascular diseases in adults in Brazil - Fernanda Sabini Faix Figueiredo; Thamires Fernandes Cardoso da Silva Rodrigues; Anderson da Silva Rêgo; Luciano de Andrade; Rosana Rosseto de Oliveira; Cremilde Aparecida Trindade Radovanovic (Universidade Federal do Rio Grande do Sul, 2020)
ABSTRACT Objectives: To analyze the distribution and spatial autocorrelation of the hospitalization rates for cardiovascular diseases in adults, and to verify the correlation with socioeconomic and health factors in Brazil. Methods: An ecological study of hospitalization rates for cardiovascular diseases in adults from 2005 to 2016. Spatial dependence was analyzed by the Moran Global and Local autocorrelation coefficients. The correlation between hospitalization rates and socioeconomic and health variables was calculated using the Spearman's correlation coefficient. Results: The highest hospitalization rates were observed in the states of Santa Catarina, Paraná, São Paulo, and Mato Grosso, with high-high autocorrelation clusters for ischemic heart disease. The hospitalizations for cardiovascular diseases were strongly correlated with low schooling, alcohol consumption, and diagnosis of hypertension. Conclusion: The high rates of hospitalization in the states mentioned, linked to socioeconomic and health factors, suggest public policies focused on the theme.